Nature’s contributions to people: Coproducing quality of life from multifunctional landscapes - Bruley, E.; Locatelli, Bruno; Lavorel, S. (Resilience Alliance, Inc., 2021)
Nature’s contributions to human well-being within social-ecological systems have been widely studied using multiple conceptual frameworks, yet there is a growing need to better articulate how both humans and nature contribute to quality of life. We present an operationalization of the Intergovernmental Platform on Biodiversity and Ecosystem Services (IPBES) conceptual framework with an in-depth analysis of the coproduction of nature’s contributions to people (NCP) in a mountain social-ecological system. Based on a participatory process questioning stakeholders on nature’s contributions to their quality of life, we propose an analysis of NCP coproduction mechanisms in a multifunctional landscape. We refine the consideration of NCP coproduction in the IPBES framework by distinguishing three coproduction types at different steps of the benefits flow from ecosystems to quality of life: (1) ecosystem management; (2) mobilization, harvesting, and physical access; and (3) appropriation, social access, and appreciation. For each of these coproduction types, we describe the types of natural and human-derived capital involved. This approach highlights: nature’s key contributions to people as perceived by participants; landscape multifunctionality and interlinkages among NCP induced by their simultaneous coproduction to improve quality of life; and a gradient of natural and human-derived capital among coproduction types and among material, nonmaterial, and regulating NCP. This approach documents how NCP coproduction creates social-ecological trade-offs and synergies among multiple NCP, as well as collaborations and conflicts among beneficiaries at the landscape level. We conclude that the analysis of NCP coproduction can provide new opportunities for ecosystem services research by tackling the involvement of both humans and nature in quality of life objectives.